SEMANTIC CLASSIFICATION OF HOLIDAY NAMES IN ENGLISH AND UZBEK LANGUAGES - Mengboyev Azizbek Alijon ugli (Western European Studies, 2025)
This article focuses on the semantic classification of holiday names in English and Uzbek languages. It explores the cultural, historical, and linguistic aspects embedded in the names of holidays, dividing them into thematic groups. The study highlights the similarities and differences between the two languages, emphasizing how cultural and social traditions shape holiday naming conventions. Through comparative analysis, it examines the influence of religion, history, and globalization on holiday names
Keywords: holidays; semantics; English